Shrub facilitation increases plant diversity along an arid scrubland-temperate rain forest boundary in South America - Zonneveld, M.J. van; Gutiérrez, J.R.; Holmgren, M. (Wiley, 2012)
Theoretical models predict nurse plant facilitation enhances species richness by ameliorating stressful environmental conditions and expanding distributional ranges of stress‐intolerant species into harsh environments. We studied the role of nurse facilitation on the recruitment of perennial plants along an arid scrubland–temperate rain forest boundary to test the following predictions: (1) nurse shrub canopy increases seedling abundance and species richness along the rain forest–scrubland boundary; (2) scrubland species are less dependent on facilitative interactions than temperate rain forest species, especially at the moister, upper end of the gradient.Bosque Fray Jorge National Park, north‐central Chile, South America (30° 39′ S – 71° 40′ W).We examined seedling abundance and species richness of perennial plants in the open and under different types of patches that may facilitate species recruitment (living shrubs, dead shrubs, perennial grasses and trees) along an arid scrubland–temperate rain forest boundary. To assess whether the potential role of the shrub canopy on seedling survival in the scrubland and forest differs, we designed a 2 × 2 factorial field experiment with shrub canopy (under shrub or open patch) and small mammal herbivory (access or closed) as factors. At both sides of the scrubland–forest gradient, we planted young seedlings of scrubland (Senna cumingii) and forest (Myrceugenia correifolia and Griselinia scandens) species under the four treatment combinations.Nurse living shrubs increased seedling abundance and diversity. Under living shrubs, the number of recruiting species was 100% and 30% larger than in open patches of the arid scrubland and temperate rain forest patches, respectively. Seedling abundance was 60% and 300% larger under living shrubs compared to open patches of the scrubland and the temperate rain forest, respectively. Despite their low cover, dead shrubs were particularly important for recruitment of young seedlings in the scrubland. Seedlings of forest species were extremely rare. The field experiment demonstrated the importance of nurse plant facilitation for the survival of the forest species at both sides of the boundary. In contrast, scrubland species were less dependent on nurse plants than forest and intermediate forest–scrubland species.Our results show that facilitative interactions increase seedling abundance and species richness along an arid scrubland–temperate rain forest boundary, notably by enhancing seedling establishment of forest species. Despite increasing nurse shrub–seedling competition in the arid scrubland, shrubs have a net positive effect on plant community diversity.